Duration of Transient Pressure of Single- Phase Flow in Porous Media - Al-Mossawy, Mohammed Idrees (2010)
The present study investigates experimentally two factors affecting the duration of transient pressure of single-phase flow in porous media. The factors that have been investigated are the permeability and flow rate. The experiments included brine flooding in sandstone cores having different permeability. The analysis methodology included calculating derivative of the pressure drop to determine exactly how many injected porevolumes are required to reach the steady-state flow (PVSS). The derivative curves have shown clearly the stages of transient pressure. It was found that PVSS decreases as permeability increases. This influence of permeability on PVSS is a function of the permeability range and different scenarios of the flow-rate changes. An empirical formula has been developed to calculate duration of the transient pressure when increasing the flow rate. There was a good matching between the suggested formula and the actual data. The present formula is useful for lab calculations to predict duration of the core-flooding experiment. The formula has an advantage that it can be used at any initial flow rate.